CFD analysis on passenger car model for drag reduction / Lim Chee Hong, M. Govardhan and Mohammed Kamel Wan Ibrahim - Lim, Chee Hong; Govardhan, M.; Wan Ibrahim, Mohammed Kamel (2006)
The aerodynamic drag experienced by a vehicle is related to the structure of the flow in its wake. Hence experimental and computational studies are initiated on a typical passenger car. Wind tunnel testing and CFD analysis was performed on a 1/6 scale model of a Mercedes-Benz C45 model complete with 77 pressure tappings on the centerline contour. Accuracy of the model was preserved with fine details such as mirrors, bumpers, sides trips and wheel housing. The vehicle yaw angle was varied from +15° to -15° and was shown to have a strong influence on the flow characteristics. Flow visualization via wool tuft technique at various yaw angles enabled the visualization of vortex formation along the A-posts and turbulence with flow separation at the rear end of the vehicle. Drag force was measured using experimental methods which yield drag coefficient values close to manufacturer claims. Extensive pressure measurements along the centerline including the front and rear diffuser area showed change in stagnation areas as the yaw angle of the car was increased. Data indicated well attached flow up to the top of the front screen. Stagnation points were visible at the front bumper area with flow separation starting at the end of the roofline. Experimental data was then compared with CFD software (COSMOS-FLOWORKS 2004) utilizing time dependent Navier-Stokes equations. The pressure distribution on the car surface correlated well with wind tunnel data.